Measuring Health Vulnerability: An Interdisciplinary Indicator Applied to Mainland Portugal - Oliveira, null (2019)
Health promotion and inequality reduction are specific goals of the United Nations 2030 Agenda, which are interconnected with several dimensions of life. This work proposes a composite index SEHVI—socioeconomic health vulnerability index—to address Portuguese population socioeconomic determinants that affect health outcomes. Variables composing SEHVI are aligned with the sustainable development goals considering data and times series availability to enable progress monitoring, and variables adequacy to translate populations’ life conditions affecting health outcomes. Data for 35 variables and three periods were collected from official national databases. All variables are part of one of the groups: Health determinants (social, economic, cultural, and environmental factors) and health outcomes (mortality indicators). Variables were standardized and normalized by “Distance to a reference” method and then aggregated into the SEHVI formula. Several statistical procedures for validation of SEHVI revealed the internal consistency of the index. For all municipalities, SEHVI was calculated and cartographically represented. Results were analyzed by statistical tests and compared for three years and territory typologies. SEHVI differences were found as a function of population density, suggesting inequalities of communities’ life conditions and in vulnerability to health.